The Impact of Covid-19 on the Development of Various Business Sectors - Sunarmin Sunarmin; Ahmad Junaidi; Endah Fantini (Ilomata International Journal of Management, 2021)
Outbreaks of the new corona virus or Corona Virus Disease 2019 (Covid-19) are increasingly felt in the domestic economy, especially in terms of consumption, corporate, financial sector, and Micro, Small and Medium Enterprises (MSMEs). The existence of Large-Scale Social Restrictions (PSBB) that has been declared by the government most of the activities involving the public are restricted, such as offices or offices that are closed, restrictions on religious activities and restrictions on public transportation. The business world has not been separated from the shadows of the Corona Covid-19 pandemic. Instead of diminishing, some countries have confirmed that they will experience a second wave of pandemic that began in Wuhan, China. The purpose of this study is to find out whether the impact of Covid-19 will have a widespread effect on business entities and the sustainability of business entities. This research is a descriptive study, using the literature method where research is conducted by studying and collecting data from libraries related to tools, both in the form of journals and scientific studies of research that has been published in public journals. The results of the study concluded that the impact on Covid-19 had a significant influence on the development of the business world. The biggest influences occur in the mall/supermarket, hospitality, manufacturing and various businesses related to the use of mass labor. In this study, not many scientific writers have focused on examining the impact of this 19 on the business world in general. Although the fact in the field of influence of Covid-19 is clearly seen the fact in the life of the wider community due to many businesses limit / lay off and even deduct workers' income from the value of income received.